RANCANG UNIK PRODOK KERAMIK - Dwi Agus Susilo; Arianto Arianto; Aurel Maylana Azhar (SULUH: Jurnal Seni Desain Budaya, 2020)
Today's modern lifestyle is very influential on human activities, as well as the facilities and infrastructure used to assist their activities. In general, people want something that is simple, practical and comfortable. This can be seen when humans do activities at home.The terrace is one of the rooms that is currently experiencing additional functions, which is usually only for receiving guests, currently there are many things that can be done on the terrace, such as sitting back, chatting, gathering with family, friends or relatives, playing. The terrace is currently located not only in front of the house, it can be on the side, behind, above (balcony).The combination of wood and stainless materials is an option in making patio chairs and tables, with a simple design, which is one of the products that humans need for their patio space. Chair and table designs can be placed in any type of terrace, creative and new designs make these chairs and tables a point of interest on the terrace.